Pertumbuhan Stek Bibit Tanaman Sukun (Artocarpus altilis) dengan Pemberian Pupuk Organik dan Plant Growth Promoting Rhizobacteria (PGPR) dari Akar Bambu - Numba, Sudirman; Robbo, Anwar; Yani, Tri (Journal Galung Tropika, 2023)
The breadfruit plant (Artocarpus altilis) can be cultivated as a staple food to accompany rice to support the diversification of food consumption found in many regions in Indonesia. Apart from being a food-producing plant, breadfruit plants act as pioneering plants for reforestation, land conservation, and medicinal plants. The research aims to determine the effect of goat drum fertilizer and PGPR on the growth of breadfruit plant seed cuttings. The research used a Randomized Block Design (RAK) with a factorial analysis of two factors and three replications. The first factor is the dose of goat manure, which consists of 4 levels: control (without fertilizer), 100g polybag-1, 200g polybag-1, and 300g polybag-1. The second factor is the PGPR concentration from bamboo roots, which consists of 4 levels: control (without PGPR), 115ml L-1, 125ml L-1, and 135ml L-1. The research results show that using a 300g polybag-1 dose of goat drum fertilizer has a natural effect and tends to be better on the parameters of shoot emergence time, shoot length, number of leaves, and root length. Meanwhile, the PGPR concentration of bamboo roots at a concentration of 135mlL-1 significantly affected all parameters measured. The interaction between the dose of goat drum fertilizer and the PGPR concentration of bamboo roots had no significant effect on the growth of breadfruit plant root cuttings.